SISTEM HUKUM INTERNASIONAL DAN PERADILAN INTERNASIONAL - Kt. Diara Astawa (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
In this globalization era, cooperative relationships spread. The relationship between one country and another is as if no border. Problems arousing are also more complicated as the increasing of the people’s needs. Law has very important roles in regulating those relationships. International law is crucially needed in maintaining harmonious relationships among people and countries. This writing is focusing in the definition of international legal system; principles, source, and subject of international legal system; causative factors and ways how to solve international disputes.